EVALUATING THE IMPACT OF RECRUITMENT PROCESS OUTSOURCING ON EMPLOYEE PERFORMANCE IN SELECTED BANKS OF NAGPUR - Wankhede, Rahul Bhagwan; Sahurkar, Avinash Madhukarrao (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Banks have begun to see Recruitment Process Outsourcing as a strategic instrument that may improve performance while optimizing procedures. This study assessed the effect of RPO on workers at banks in Nagpur. Important aspects like recruiting effectiveness, employee productivity, work satisfaction, and retention rates were investigated. Surveys and interviews with HR experts and bank employees were conducted to evaluate RPO's efficacy. Results showed RPO considerably improved recruiting quality, decreased vacancy fill times, and increased engagement. However, difficulties integrating with corporate HR policies and relying on external suppliers were also illuminated during discussions. This research offers financial organizations contemplating RPO as a means to enhance staff performance useful insights that can increase operational efficiency.